SPEECH ACTS OF NETIZENS TOWARD SURAKARTA MAYOR’S INAUGURATION OF GIBRAN RAKABUMING RAKA: A STUDY OF ANTHROPROPRAGMATICS - Dini Restiyanti Pratiwi; Eko Purnomo; Agus Budi Wahyudi; Tri Santoso (Universitas Muhammadiyah Semarang, 2021)
Gibran, the eldest son of the President of the Republic of Indonesia, won the election and currently serves as Surakarta Mayor for the period 2021-2026. Netizens’ Surakarta have great hopes for his leadership. Gibran’s inauguration attracted spotlight, because he is the first child in the Republic of Indonesia (Ir. Joko Widodo). The formulations of the research problems are: (1) What is the form of speech acts of netizens toward Gibran’s inauguration pragmatically? And (2) What is the form of speech acts of netizens toward Gibran’s inauguration anthropolinguistically? This study aims (1) to describe the form of netizens’ speech acts toward Gibran's inauguration pragmatically, (2) to describe the form of netizens’ speech acts toward Gibran's inauguration anthropolinguistically. This research is included in a qualitative with description approach. The data are in the form of speech acts which contain pragmatic and anthropolinguistic aspects of netizens comments. The data source is written language taken from the Instagram comments column that posted Gibran's inauguration. The data collection technique used was the observation and taking note techniques. Methods of data analysis uses intralingual equivalents in the form of pragmatic equivalents and antroprolinguistics. The results indicate that in netizens’ comments there are speech acts in a pragmatic manner, namely locutionary, illocutionary, and perlocutionary. Apart from being pragmatics, there are antroprolinguistic speech acts, namely saying congratulations, being happy, hoping/asking, and giving advice. The speech acts of the netizens’ Surakarata, both pragmatically and anthropolinguistically (anthropopragmatically), aim to accept a new leader and define Javanese culture.